PENGARUH PENGGUNAAN MADU DALAM ORAL HYGIENE TERHADAP STATUS KESEHATAN MULUT PADA PASIEN PNEUMONIA YANG TERPASANG INTUBASI DI RUANG ICU RSUD SITI FATIMAH AZ-ZAHRA PROVINSI SUMATERA SELATAN TAHUN 2022 - Nurjannah; Deah Karina Saputri; AnI Syafriati (Jurnal Kesehatan dan Pembangunan, 2023)
Pneumonia is an acute infectious disease affecting the tissues of the lungs caused by several microorganisms such as viruses, bacteria, fungi, and other microorganisms. Ventilator-associated Pneumonia (VAP) is still a serious matter that must be treated and prevented. One of the ways to prevent VAP is through oral care or oral hygine. The use of honey in oral hygiene is useful for overcoming oral health problems. Honey contains antibacterial substances, antibiotics as well as disinfectants which are very effective at inhibiting the growth of pathogenic bacteria in the mouth. A pre-experimental design approach (One Group Pre Post Test Design) was used in this study. The subjects of this case study were a pneumonia patients who were intubated. The author conducted 4 observations of oral health status using the Oral Assessment Scale (OAS) observation sheet. The results of this study revealed that the parametric statistical test resulted in a p value = 0.000 (p value <0.05) indicatingthat there was a significant different effect between oral hygiene before using honey and after using honeyon the oral health status of pneumonia patients who were intubated in the ICU of Siti Fatimah Hospital, South Sumatra Province. It is suggested that the medical personnels, especially nurses, apply oral hygiene interventions using honey to improve oral health status of intubated patients who are treated in the ICU.